MEMBANGUN NIAT BELI IPHONE MELALUI EWOM DAN BRAND IMAGE - Darmawan, Rizky; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 7 No 9 (2018), 2018)
ABSTRACT   Intention to buy is the intention of someone in a buying process, whether the person intends to buy the product or not. The purpose of this research is to know the effect of EWOM on brand image, EWOM influence to purchase intention, influence of brand image to purchase intention and brand image role in mediating EWOM relationship with intention to buy Iphone product. The population in this study is the citizens of Denpasar who intend to buy Iphone products. Determination of the sample in this study using purposive sampling technique. The number of samples taken as many as 110 people. Analysis technique used is path analysis technique or path analysis and Sobel Test. The findings of this study indicate that there is a positive and significant relationship between EWOM with brand image, EWOM with the intention to buy, brand image with the intention to buy. Brand image can act as a mediating variable between EWOM influence with purchase intention. These results indicate that a positive EWOM can improve the brand image and can increase consumer purchase intentions towards Iphone products. Keywords: brand image, EWOM , purchase intention